2009
DOI: 10.1523/jneurosci.3359-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial EEG Reveals a Time- and Frequency-Specific Role for the Right Inferior Frontal Gyrus and Primary Motor Cortex in Stopping Initiated Responses

Abstract: Inappropriate response tendencies may be stopped via a specific fronto/basal ganglia/primary motor cortical network. We sought to characterize the functional role of two regions in this putative stopping network, the right inferior frontal gyrus (IFG) and the primary motor cortex (M1), using electocorticography from subdural electrodes in four patients while they performed a stop-signal task. On each trial, a motor response was initiated, and on a minority of trials a stop signal instructed the patient to try … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

54
361
6
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 418 publications
(423 citation statements)
references
References 61 publications
(110 reference statements)
54
361
6
2
Order By: Relevance
“…The current results support this claim. At 175 ms, the timing of rIFG's effect in the current experiments is reminiscent of the timing of changes in synchrony recorded in this area during action inhibition (8). Despite the evidence that rIFG induces inhibition at a physiological level when cognitive control is needed, it should also be emphasized that the part of rIFG we investigated here (SI Text Section 1) exerted an excitatory influence on M1 corticospinal activity during routine action selection on "stay" trials.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…The current results support this claim. At 175 ms, the timing of rIFG's effect in the current experiments is reminiscent of the timing of changes in synchrony recorded in this area during action inhibition (8). Despite the evidence that rIFG induces inhibition at a physiological level when cognitive control is needed, it should also be emphasized that the part of rIFG we investigated here (SI Text Section 1) exerted an excitatory influence on M1 corticospinal activity during routine action selection on "stay" trials.…”
Section: Discussionmentioning
confidence: 63%
“…The rIFG has a preeminent role in a network for action inhibition because it inhibits M1 corticospinal activity during action reprogramming 175 ms after a visual cue, indicating that a change in action is needed (SI Text Section 2). It has previously been suggested that rIFG might exert its influence over other brain areas by inhibiting physiological activity (8), but this has been difficult to test empirically. The current results support this claim.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this multimodal study, a frontocentral increase of beta power starting at about 400-500 ms after an erroneous response showed a positive correlation with PES on the next correct trial. Importantly, this beta oscillatory component (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) has been linked to motor inhibition (Whittington et al, 2000;Alegre et al, 2004;Kramer et al, 2009;Swann et al, 2009;Walsh et al, 2010). Our results might be compatible with these findings, since the increase of excitability of the ipsilateral motor cortex at 450 ms occurred roughly at the same time as the betaoscillatory component associated to PES (see Danielmeier and Ullsperger, 2011 for a discussion).…”
Section: Discussionmentioning
confidence: 99%
“…This hyperdirect pathway assumes projections of the frontal cortex (pre-SMA, inferior frontal gyrus and anterior cingular cortices) onto the subthalamic nucleus (Haynes & Haber, 2013). This hypothesis is attractive, but it is currently only supported by a few intracerebral electrophysiological recordings in humans-during the stop signal task (SST)-showing that beta (15e35 Hz) oscillations of local field potentials (LFP) increased during stopping in the inferior frontal gyrus (Jha et al, 2015;Swann et al, 2009;Wessel, Conner, Aron, & Tandon, 2013) and in the STN at latencies that precede the time needed to cancel movements (stop signal reaction time, SSRT). Indirect evidence also comes from reports that showed that STN lesions cause ballistic and involuntary movement in non-human primates and humans (Crossman, Sambrook, & Jackson, 1984;Nishioka, Taguchi, Nanri, & Ikeda, 2008) as well as inaccurate and premature responding in reaction time tasks performed by rats (Baunez, Nieoullon, & Amalric, 1995;Eagle et al, 2008) and humans (Obeso et al, 2014).…”
Section: Introductionmentioning
confidence: 99%